Inovasi Blended Learning Dalam Pembelajaran Bahasa Arab: Tantangan dan Peluang di Era Society 5.0 - Arani, Samsuar; Muslimah, Hidayatil; Zikriati, Zikriati; Zulhendra, Danil (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2024)
Innovation in the field of education has become increasingly important in the era of Society 5.0, where smart technologies such as AI, Internet of Things (IoT), and big data are integral parts of everyday life. Arabic language learning must also adapt by utilizing Blended Learning methods, which combine face-to-face and online learning to create a more flexible and effective learning experience. However, the implementation of this method faces various challenges, such as technological readiness, digital literacy, and shifts in educational paradigms, particularly in environments that still maintain conventional learning traditions. On the other hand, Blended Learning offers significant opportunities to enhance personalized learning, accessibility, and global collaboration. This research aims to analyze the challenges and opportunities of Blended Learning in Arabic language learning in the era of Society 5.0. Through a literature review, this study explores the concept of Blended Learning, the impact of Society 5.0 on education, innovations in Arabic language learning, and strategies to overcome the challenges of Blended Learning implementation. The results indicate that the wise use of technology and the readiness of educational institutions are key to successfully integrating Blended Learning to improve the quality of Arabic language learning in the digital era.